2017
DOI: 10.1080/00332747.2016.1208002
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic Depression and Suicidal Behavior

Abstract: Suicide risk assessments based on verbal reports from individuals with psychotic depression may not always be valid due to potential impulsivity and underreporting of suicidal ideation. It may be important for clinicians to explore the delusional content of such patients' experiences to assess the possibility of suicide as a result of shame, guilt, remorse, or altruistic intentions to save others from harm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 33 publications
7
26
0
1
Order By: Relevance
“…Our findings have important clinical implications as patients with PMD frequently avoid expressing their psychotic experiences, being unable to deal with their psychotic phenomena and strong feelings of guilt, shame, intense anxiety, fear, etc . Additionally, they are often too psychomotorly retarded to give adequate verbal information about their psychotic experiences; thereby, their psychosis is often overlooked .…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Our findings have important clinical implications as patients with PMD frequently avoid expressing their psychotic experiences, being unable to deal with their psychotic phenomena and strong feelings of guilt, shame, intense anxiety, fear, etc . Additionally, they are often too psychomotorly retarded to give adequate verbal information about their psychotic experiences; thereby, their psychosis is often overlooked .…”
Section: Discussionmentioning
confidence: 84%
“…Fifty studies were left for further investigation after exclusion of duplicates and irrelevant to the research question references. Eight studies reported data on completed suicides , nine included bipolar patients , five had no comparison group , five assessed suicidality by means of psychometric scales with no categorical data , two consisted of the same sample with the included studies , and two were excluded because their sample exclusively comprised patients with history of suicidal attempt or adolescent ones with psychotic experiences without fulfilling PMD criteria though .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression, also known as depressive disorder, is characterized by overwhelming and persistent feelings of sadness and worthlessness. Severely depressed patients may have suicidal thoughts and behavior . The 2017 Global Burden of Disease (GBD) study identified depression as the 3rd cause of disability and the 15th contributor to the burden of disease as measured by disability life years (DALYs), with an increase of more than 10% in 2007 .…”
Section: Introductionmentioning
confidence: 99%
“…Noen pasientgrupper i psykiatriske avdelinger har høy/økt forekomst av selvmord under innleggelse og rett etter utskrivning (8). Disse pasientene er preget av agitasjon, panikk, desperasjon og av og til psykose (9). De siste 20 årene har vi fått kunnskap om at den primaere suicidforebyggende behandlingen for denne gruppen bør vaere å sikre adekvat behandling av angst og søvn (10).…”
unclassified